A Generalized Review on Extraction of Biomolecules - Shireen, S.; Zarena, A.S. (Journal of Pharmacy and Nutrition Sciences, 2022)
Nature has given us a wide range of biological compounds that can be utilized to help combat health problems, but sometimes with over-processing, these advantages are diminished or lost. Food and pharmaceutical companies have developed a range of new approaches to harness and retain the naturally occurring diversity and quality of bioactive compounds efficiently and effectively. Pharmaceutically important plant products have been known for millennia; they have been used in crude and unrefined forms. One of the best ways to pick the best plant bioactive is through genetic engineering, omics, and plant tissue culture. Many laboratories routinely screen plant species for bioactive compounds to discover new ones. All extraction methods depend on the researcher’s preference and what exactly the research entails. Successful extraction begins with the careful selection and preparation of plant samples and thorough knowledge and review of the appropriate literature. Here we have attempted to describe the different stages and methods of extraction from the medicinal plants. From the review, it can be concluded that no universal extraction method is ideal and that each extraction procedure is unique.